Assessment of Level of Collimation for Pediatric Plain Chest Radiographs in a Teaching Hospital in Kano, Northwestern Nigeria (Journal of Nuclear Technology in Applied Science, 2020)
Collimation of x-ray beam is an important factor in optimization; good collimation will both minimize the radiation dose to the patient and improve image quality because the amount of scattered radiation will increase as if a large volume of tissue is irradiated. This study aimed to assess the level of collimation for pediatric plain chest radiographs in Aminu Kano Teaching Hospital as an optimization tool.  A retrospective audit was conducted on pediatric plain chest radiographs from May 2016 to May 2019 in Aminu Kano Teaching Hospital (Kano, Nigeria) using a simple random sampling technique. Data were collected and recorded using self-developed data capture sheet based on the European Guidelines on quality criteria for diagnostic radiographic images in pediatrics which captures the gender, age, projection, collimation (4 ways, 3 ways, 2 ways, 1 way, no and under collimation). The results showed that the most predominant age group exposed in the study was within 0 to 1 year representing 31.7% (n=76). Also gender distribution showed that more male were exposed than female, representing 55% (n=132). Out of 240 plain chest radiographs, about 77.0% (n=175), showed inadequate collimation. In conclusion,the study revealed poor collimation practice in pediatric plain chest radiographs.
Keywords: Pediatrics; Optimization; Collimation; Radiation protection; Image quality